Current Advances on Zn Anodes for Aqueous Zinc‐Ion Batteries. Issue 11 (10th August 2021) - Li, Xin; Zeng, Jiaming; Yao, Hong; Yuan, Du; Zhang, Liping
Abstract: As the representative in rechargeable multivalence ion batteries, aqueous zinc ion battery (ZIB) is a promising safe and green solution in the post‐lithium ion era. Though ZIB is being intensively investigated due to its unique merits, the development of ZIB is facing the fundamental obstacles during Zn stripping/plating, namely, zinc dendrite formation, hydrogen evolution, and solid‐electrolyte interface (SEI) formation, which severely affect the cycling stability of ZIB. In this minireview, we aim to provide current aspects of novel approaches to deal with the above critical issues. The approaches are discussed from the perspectives of regulation of electrolyte, construction of Zn anode, and design of surface coating or SEI layer, where their effects on Zn deposition and surface evolution are focused. Last, the challenges and outlooks on the current approaches towards highly reversible Zn anode are presented for the development of ZIB. Abstract : The development of highly reversible Zn anodes for zinc‐ion batteries is driven by the fundamental understanding on the chemistry/electrochemistry at the Zn surface.